Checking the effectiveness of modern technologies in the work of a psychologist with firefighters-rescuers - Fomych Mykola Volodymyrovych (Insight: the psychological dimensions of society, 2023)
Some aspects of the problem of the psychological support of the professional activity of firefighters rescuers of the State Emergency Service of Ukraine are analyzed in the article. It is found out that such activity is classified as complex and dangerous, connected with a high level of psychoemotional pressure that leads to a deterioration of functional states and a decrease in work capacity. The necessity of using the modern technologies containing appropriate forms and methods of mental recovery of workers of the mentioned above sphere of work in the process of psychological support is substantiated, and can be used by a psychologist in the work of the psychological relief room, but in order to determine effectiveness, they require the experimental evaluation. The purpose of the research is to experimentally check the effectiveness of the use of modern technologies of work of a psychologist in the psychological relief room for firefighters-rescuers. Methods. To achieve this purpose, a complex of psychodiagnostic and psychophysiological research methods was used in our research, including the method of assessing the level of mental work capacity based on the quasi-stationary potential magnitude, the method of studying changes in the overall activation of the cerebral hemispheres, Luscher color test, the method of diagnosing mood, activity, and feelings, dynamometry, methods of interviewing, and analysis of the results of official activities. Results. The empirical assessment of the effectiveness of the corresponding forms and methods was carried out with the involvement of two groups of firefighters-rescuers of the State Emergency Service of Ukraine. It was found out that in the control group of the firefighters-rescuers who were not subjected to recovery methods, the functional state worsened after completing the tasks of the activity, while in the experimental group of the firefighters rescuers who were subjected to recovery effects, the functional state significantly improved. In particular, the optimization of the functional state occurred while using the neuromuscular relaxation and breathing exercises in combination with aromatherapy. Functional music and self-massage of biologically active points were also found to be effective. In turn, the use of phyto-therapeutic methods, in particular, drinks made of the medicinal plants, did not show a statistically significant result. During the study the effectiveness of VR-methods usage in the process of psychological training of the firefighters rescuers of the State Emergency Service of Ukraine to form individual components of resistance to the effects of the professional activity was also confirmed. Conclusions. Thus, the researched techniques can be used in the practical work of the psychologist in the psychological relief room for firefighters rescuers for the purpose of recovering and optimizing functional states, and forming psychological readiness for the tasks of professional activities of extinguishing fires and liquidating the consequences of emergencies of man-made, natural and military nature.